Non-contiguous finished genome sequence and description of Alistipes timonensis sp. nov. Issue 3 (May 2012) - Lagier, Jean-Christophe; Armougom, Fabrice; Mishra, Ajay; Nguyen, Thi-Tien; Raoult, Didier; Fournier, Pierre-Edouard
Abstract Alistipes timonensis strain JC136T sp. nov. is the type strain ofA. timonensis sp. nov., a new species within the genusAlistipes . This strain, whose genome is described here, was isolated from the fecal flora of a healthy patient.A. timonensis is an obligate anaerobic rod. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 3, 497, 779 bp long genome (one chromosome but no plasmid) contains 2, 742 protein-coding and 50 RNA genes, including three rRNA genes.